TUANGKU: Antara Tradisi dan Locak Religious Authority - Zakirman, Zakirman; Mahmudi, Elva; Bary, Shafwatul (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2023)
The issues of religious authority are at the center of debate and contestation in various aspects of Islam in the modern world. These issues have been discussed and widely debated long before the major political, economic, and intellectual transformations that Muslim societies have undergone since the nineteenth century. The authority of Muslim scholars, was largely unquestioned before the emergence of new authorities aided by modern media. Interestingly, in Padang Pariaman Regency, West Sumatra, religious figures with authority are referred to as Tuangku. On one hand, the community's resistance to the authority of Tuangku ensures their continued existence as the sole holders of control. On the other hand, this dynamic negates the possibility of fragmentation and contestation with other religious authorities. This study seeks to answer two key questions: (1) What is the position of Tuangku's religious authority in Padang Pariaman Regency? (2) What dynamics affect the authority of Tuangku as transmitters of Islamic teachings in the Padang Pariaman community? Using a qualitative, descriptive-analytical approach based on interview data, the study argues that local religious authorities like Tuangku have become well-established and remain resilient against the forces of globalization and media openness. The phenomenon of new authorities born from modern media is not seen as a significant threat to the people of Padang Pariaman, a result of the community's resistance, which is also nurtured by the Tuangku.